2016
DOI: 10.1111/jan.12926
|View full text |Cite
|
Sign up to set email alerts
|

Instruments for measuring meaningful learning in healthcare students: a systematic psychometric review

Abstract: The systematic review produced a synthesis of the psychometric properties of tools that measure learning outcomes in students of healthcare disciplines. Measuring learning outcomes is very important when educating health professionals. The identified tools may constitute a starting point for the development of other assessment tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
1
15
0
2
Order By: Relevance
“…This study, by building this instrument contributes to bridging a gap that recently emerged from the literature: the need to measure the results of significant learning in healthcare students (Magnussen , Marrocco , Cadorin et al . ). Moreover, this approach enables adult students to become involved in the process of change by exploiting their own experience, thereby making them responsible for their own learning (Marrocco ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This study, by building this instrument contributes to bridging a gap that recently emerged from the literature: the need to measure the results of significant learning in healthcare students (Magnussen , Marrocco , Cadorin et al . ). Moreover, this approach enables adult students to become involved in the process of change by exploiting their own experience, thereby making them responsible for their own learning (Marrocco ).…”
Section: Discussionmentioning
confidence: 97%
“…) to identify and implement strategies that can support the skills of students or professionals, with a view to increase their awareness and responsibility during the course of learning. In the literature, several instruments that measure individual proclivity to 'Deep Learning', in the sense of disposition or style, have been identified (Cadorin et al 2015), as conceptual maps have been used to evaluate cognitive aspects such as the acquisition of concepts and prepositions (Novak 2001). By contrast, no instruments that specifically measure the affective and behavioural abilities of 'Significant Learning' have been found (Fink 2003, 2007, Cadorin et al 2015.…”
Section: Why Is This Study or Review Needed?mentioning
confidence: 99%
See 1 more Smart Citation
“…When learning strategies are used correctly by the students and supervisors they help towards a better understanding of one's own responsibility for learning. In a review, Cadorin et al, [14] found that the use of strategies stimulates student progress and helps the student to become more aware of their shortcomings. Accordingly, students need to practice writing their own learning strategies effectively and this should be implemented at an earlier stage in nursing education, hence also promoting a student-centred learning environment.…”
Section: Facilitation or Hindrance In Assessmentmentioning
confidence: 99%
“…[8] Enabling nursing students to write personal learning strategies helps promote the development of meaningful learning. [14] Consequently, the development of a clinical assessment tool that sets goals for achievement and provides possibilities for specific feedback on learning is important within the assessment process. [15] Maintaining quality assessment of nursing students' professional competence, learning strategies and adequate feedback during clinical practice is still a challenge.…”
Section: Introductionmentioning
confidence: 99%